Sex and the City: Silens and Nymphs in Ancient Greek Pottery - Diez Platas, Fátima (Eikón / Imago, 2013)
This paper deals with the images of Silens and Nymphs together, especially in erotic scenes on black-figure vases from the sixth century B. C., usually considered as a repeated stock images, belonging to the general imagery of the Dionysiac thiasos. A further analysis on a few archaic vases shows that the erotic relationship between Silens and Nymphs have several features in common with mythic pursuit or rape scenes, and could be iconographically read as an attempt of showing an inversion of the heroic erotic values, proposing a counterpart model of the kind of wild love, which takes place in the imaginary world outside of the limits of the polis.